2016
DOI: 10.1007/s13203-015-0145-7
|View full text |Cite
|
Sign up to set email alerts
|

Modification of USY zeolites with malic–nitric acid for hydrocracking

Abstract: The modification of commercial ultra-stable Y zeolite using malic acid (MA) and nitric acid (NA) was investigated. A series of factors including the amount of MA and NA solutions, the pH of the solutions, the treatment time, and the reaction temperature were investigated and optimized. The pore structure, acid properties, and crystal structure of modified USY zeolite were characterized by N 2 -adsorption, temperature-programmed desorption of ammonia (NH 3 -TPD), pyridine adsorbed Fourier transform infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Dealuminization is an efficient method to increase the ratio of Si/Al by transferring framework Al into an extra-framework position and then being washed away. , Xin-Mei et al modified a USY zeolite with citric acid and obtained improved a Si/Al ratio Y zeolite with smaller unit cell parameters. Qiao et al., by malic acid and nitric acid treatment, studied the modified USY zeolites and found that the aluminum removed by a coordination reaction of MA could create extensive secondary pores, while NA could only remove alumina of extra framework. In most of these studies, the nature of framework and extra-framework aluminum was characterized on 27 Al MAS solid-state NMR by determining the Al coordination with high resolution .…”
Section: Introductionmentioning
confidence: 99%
“…Dealuminization is an efficient method to increase the ratio of Si/Al by transferring framework Al into an extra-framework position and then being washed away. , Xin-Mei et al modified a USY zeolite with citric acid and obtained improved a Si/Al ratio Y zeolite with smaller unit cell parameters. Qiao et al., by malic acid and nitric acid treatment, studied the modified USY zeolites and found that the aluminum removed by a coordination reaction of MA could create extensive secondary pores, while NA could only remove alumina of extra framework. In most of these studies, the nature of framework and extra-framework aluminum was characterized on 27 Al MAS solid-state NMR by determining the Al coordination with high resolution .…”
Section: Introductionmentioning
confidence: 99%